Use, re-use or discard? Quantitatively defined variance in the functional integrity of N95 respirators following vaporized hydrogen peroxide decontamination during the COVID-19 pandemic. (January 2021) - Levine, C.; Grady, C.; Block, T.; Hurley, H.; Russo, R.; Peixoto, B.; Frees, A.; Ruiz, A.; Alland, D.
Summary: Background: Coronavirus disease 2019 has stretched the ability of many institutions to supply needed personal protective equipment, especially N95 respirators. N95 decontamination and re-use programmes provide one potential solution to this problem. Unfortunately, a comprehensive evaluation of the effects of decontamination on the fit of various N95 models using a quantitative fit test (QNFT) approach is lacking. Aims: To investigate the effects of up to eight rounds of vaporized hydrogen peroxide (VHP) decontamination on the fit of N95 respirators currently in use in a hospital setting, and to examine if N95 respirators worn by one user can adapt to the face shape of a second user with no compromise to fit following VHP decontamination. Methods: The PortaCount Pro+ Respirator Fit Tester Model 8038 was used to quantitatively define functional integrity, measured by fit, of N95 respirators following decontamination with VHP. Findings: There was an observable downward trend in the functional integrity of Halyard Fluidshield 46727 N95 respirators throughout eight cycles of decontamination with VHP. Functional integrity of 3M 1870 N95 respirators was reduced significantly after the respirator was worn, decontaminated with VHP, and then quantitatively fit tested on a second user. Furthermore, inconsistencies between qualitative fit test and QNFT results were uncovered that may have strong implications on the fit testing method used by institutions. Conclusions: The data revealed variability in the functional integrity of different N95 models after VHP decontamination, and exposed potential limitations of N95 decontamination and re-use programmes.